Optimal Design and Dispatch of Electrically Driven Heat Pumps and Chillers for a New Development Area - Pieper Henrik; Ommen Torben; Elmegaard Brian; Volkova Anna; Markussen Wiebke Brix (Environmental and Climate Technologies, 2020)
Large-scale heat pumps (HPs) and refrigeration plants are essential technologies to decarbonise the heating and cooling sector. District heating and cooling (DHC) can be supplied with low carbon footprint, if power generated from renewable energy sources is used. The simultaneous supply of DHC is often not considered in energy planning, nor the characteristics of the heat source and sink. Simplified approaches may not reveal the true potential of HPs and chillers. In this paper, different heat sources and sinks and their characteristics were considered for the simultaneous supply of DHC based on large-scale HPs and refrigeration plants. An optimization model was developed based on mixed-integer linear programming. The model is able to identify ideal production and storage capacities, heat sources and sinks based on realistic hourly operation profiles. By doing so, it is possible to identify the most economical or sustainable supply of DHC using electricity. The optimization model was applied to the Nordhavn area, a new development district of Copenhagen, Denmark. The results show that a combination of different heat sources and sinks is ideal for the case study. A HP that uses the district cooling network as a heat source to supply DHC was shown to be very efficient and economical. Groundwater and sewage water HPs were proposed for an economical supply of district heating. The Pareto frontier showed that a large reduction in annual CO2 emissions is possible for a relatively small increase in investments.